The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.18632/oncotarget.25283
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor expression and function differ between splenic marginal zone B cell lymphoma and splenic diffuse red pulp B cell lymphoma

Abstract: In splenic marginal zone lymphoma (SMZL), specific and functional Toll-like Receptor (TLR) patterns have been recently described, suggesting their involvement in tumoral proliferation. Splenic diffuse red pulp lymphoma with villous lymphocytes (SDRPL) is close to but distinct from SMZL, justifying here the comparison of TLR patterns and functionality in both entities.Distinct TLR profiles were observed in both lymphoma subtypes. SDRPL B cells showed higher expression of TLR7 and to a lesser degree TLR9, in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…While other studies have demonstrated the functional role of IL-1 and signaling pathway of TLR4 in astrocytes 51,52 , to our knowledge, this is the first time the critical autocrine/paracrine effects of TNF-α on astrocyte functioning are demonstrated. In addition, other studies have demonstrated the roles of TLRs, including TLR2 and TLR4, in upregulating proliferation in various cancers [53][54][55][56] , to our knowledge, we are the first to demonstrate their significance in the transition between quiescent and proliferative astrocytes via the production of TNF-α. Our findings will likely delineate the cellular and molecular mechanisms involved in different neurological conditions.…”
Section: Discussionmentioning
confidence: 67%
“…While other studies have demonstrated the functional role of IL-1 and signaling pathway of TLR4 in astrocytes 51,52 , to our knowledge, this is the first time the critical autocrine/paracrine effects of TNF-α on astrocyte functioning are demonstrated. In addition, other studies have demonstrated the roles of TLRs, including TLR2 and TLR4, in upregulating proliferation in various cancers [53][54][55][56] , to our knowledge, we are the first to demonstrate their significance in the transition between quiescent and proliferative astrocytes via the production of TNF-α. Our findings will likely delineate the cellular and molecular mechanisms involved in different neurological conditions.…”
Section: Discussionmentioning
confidence: 67%
“…This study demonstrates the necessity of a more profound understanding of immune effectors in SMZL TME. Other studies have concerned the innate immune system; one of them from Verney et al identified distinct TLRs profiles in SMZLs [ 80 ]. The dense CD40 expression by bone marrow stromal cells (involving CD40 ligand expressed by mast cells) is correlated with a poorer prognosis [ 81 ].…”
Section: Resultsmentioning
confidence: 99%